Making Inference across Mobilisation and Influence Research: Comparing Top-Down and Bottom-Up Mapping of Interest Systems. (February 2018) - Berkhout, Joost; Beyers, Jan; Braun, Caelesta; Hanegraaff, Marcel; Lowery, David
Scholars of mobilisation and policy influence employ two quite different approaches to mapping interest group systems. Those interested in research questions on mobilisation typically rely on a bottom-up mapping strategy in order to characterise the total size and composition of interest group communities. Researchers with an interest in policy influence usually rely on a top-down strategy in which the mapping of politically active organisations depends on samples of specific policies. But some scholars also use top-down data gathered for other research questions on mobilisation (and vice versa). However, it is currently unclear how valid such large-N data for different types of research questions are. We illustrate our argument by addressing these questions using unique data sets drawn from the INTEREURO project on lobbying in the European Union and the European Union's Transparency Register. Our findings suggest that top-down and bottom-up mapping strategies lead to profoundly different maps of interest group communities.